2008
DOI: 10.1186/gb-2008-9-2-r30
|View full text |Cite
|
Sign up to set email alerts
|

Genomic degradation of a young Y chromosome in Drosophila miranda

Abstract: Study of the recently formed neo-Y chromosome of Drosophila miranda demonstrate that degeneration of a recently formed Y-chromosome can proceed very rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
164
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 33 publications
9
164
0
Order By: Relevance
“…still harbors many functional genes. Even in this much younger Y chromosome, there is a more than 20-fold greater accumulation of repetitive sequences, mainly transposable elements, compared with that in the X chromosome (Bachtrog et al, 2008). These findings in animal species show that the accumulation of junk DNA is an important step in promoting the morphogenesis of sex chromosomes.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…still harbors many functional genes. Even in this much younger Y chromosome, there is a more than 20-fold greater accumulation of repetitive sequences, mainly transposable elements, compared with that in the X chromosome (Bachtrog et al, 2008). These findings in animal species show that the accumulation of junk DNA is an important step in promoting the morphogenesis of sex chromosomes.…”
mentioning
confidence: 62%
“…Insertion of repetitive sequences into coding genes and regulatory regions induces alteration in the genes' functions and results in gene loss. However, there is no correlation between the insertion of the transposable element and gene dysfunction on the Y chromosome of D. miranda (Bachtrog et al, 2008). Moreover, the rate of gene gain on the Drosophila Y chromosomeusing the sequences of 12 species-is more than 10 times the rate of gene loss, in contrast with the mammalian Y chromosome (Koerich et al, 2008).…”
mentioning
confidence: 88%
“…Rapid degeneration of recently formed Y chromosomes has been demonstrated in Drosophila (Bachtrog et al, 2008) and sticklebacks (Peichel et al, 2001). However, there are few empirical data for W chromosomes.…”
Section: Evolution Of Sex Chromosomes In Congeneric Speciesmentioning
confidence: 99%
“…Heterochromatinization of the region, which may have originally served as a defense against TEs, probably started, or at least accelerated, the degeneration of the MSY in the papaya (Zhang et al, 2008). Bachtrog et al (2008) showed that in the neo-Y chromosome of D. miranda there are 20 times as many TE insertions compared with the neo-X chromosome. They also show that the fraction of TE insertions is similar in functional and non-functional genes.…”
Section: Processes Acting In Regions Of Reduced Recombinationmentioning
confidence: 99%